О пищевом рационе жителей генуэзских колоний Крыма - Столяренко, Е. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary E. Stoliarenko. About the Diet of the Inhabitants of the Genoese Colonies in Crimea The article deals with the diet of inhabitants Genoese colonies in the Crimea. The author emphasizes that knowledge of the human diet is very important, because the satisfaction of hunger is one of the basic human needs. In E.M. Stolyarenko’s work products, which were known to the inhabitants of the colonies, are divided into three groups: foods of plante origin, foods animal origin and seafood. Using the written and archaeological sources, the author highlighted the main food of people of Genoese colonies in Crimea. There was also an attempt to identify priority of grains and vegetables for colonial cuisine. Inhabitants of the colonies mostly used wheat, other grasses took a secondary position. In local markets trading in many kinds of vegetables and fruits. Spices are also took an important place. Despite the fact that the meat and seafood are mentioned in written sources not often, they took a significant place in the daily diet. This is evidenced by archeological finds. In addition, there were marked prepared dish, which are mentioned in the sources, and attempt to learn their recipes and cost. The author concluded that the inhabitants of the Genoese colonies in Crimea were known almost all kinds of products of the Mediterranean cuisine those times. Key words: Genoese colonies, Caffà, diet, cuisine, foods.